INFLUENCE OF URBAN FORESTATION ON THE THERMAL COMFORT OF RESIDENTS OF JARDIM IRACEMA, FORTALEZA, CEARÁ - Edmilson Muniz, Manoel; Jeferson Sampaio Diogo, Ivan (Journal of Interdisciplinary Debates, 2021)
Urban forestation has an important connotation in the cities, being essential to contribute to the well-being of the population. The present study aimed to analyze the relationship between urban forestation and thermal comfort in an urban neighborhood of Fortaleza / CE. As specific objectives: to evaluate the influence of afforestation on microclimate factors, to compare different areas (with and without afforestation) in the Jardim Iracema neighborhood in Fortaleza / CE, and to understand the importance of trees for the population. This research was carried out in two stages: preliminary survey of the locality with subsequent application of a questionnaire with 40 people from the community and measurement of temperature and humidity in 8 different points, 4 of which are wooded and 4 not wooded. The results demonstrate that local air temperature and humidity are influenced by the presence of air. As for the environmental perception, 65% of the population is dissatisfied with the local urban forestation and they like places with trees because they bring shade (95%) and reduce the temperature (85%). However, they address harm such as interference with public lighting and the power grid. Most of the interviewees believe that the trees used do not resemble those of the caatinga domain and do not have an opinion about the pruning. Another important point is that half of the interviewees do not collaborate with the local urban forestation and believe that the public agencies must have responsibility on it. Public agencies must create strategies aimed at sensitizing the population about the importance of urban forestation and its maintenance, promoting environmental education.